Performing Piety - Kendra Salois (International Institute of Islamic Thought, 2014)
Anthropologist Karin van Nieuwkerk’s latest book-length study addresses the phenomenon, widely discussed in Egyptian media since the 1990s, of celebrated singers, actors, and dancers who withdraw from their professions to live according to what they believe are Islamically sound principles. The author of “A Trade Like Any Other”: Female Singers and Dancers in Egypt (Austin: University of Texas Press, 1995), van Nieuwkerk draws on experience and contacts from over two decades of research. But this project, as well as its subjects and issues, presents new challenges for the ethnographer. Each of the three main sections describes the trends of a particular decade. The first wave of famous women to retire began in the late 1980s, and thus the first section focuses on the shared rhetorics, ideologies, and activities of “repentant” artists. From the beginning, artists cannot be read as simply adopting wholesale Salafist ideologies, since their personal turning points bore as much influence from “popular” or “Sufi” religiosity as from the “rationalist” tendencies of Islamists (p. 30). In the early 1990s, as retirements peaked, Egyptian media became central to both celebrities’ and fans’ understanding of this new trend. In this section, the author focuses on debates over secular(ist) aesthetics and changing discourses on women’s participation in public life. Two generations of preachers offer different rationales for women’s retirements or re-entry into art, reflecting the sea change incited by a generation of Muslim Brotherhood-allied “lay preachers” such as Amr Khalid during the 1990s. The 2000s are depicted as a time of experimentation. Some veiled women choose to return to entertainment on their own terms; their productions cater to a growing market for entertainment that reflects elite consumption habits and piety, overcoming a longstanding association of overt piety with impoverished Cairenes and villagers. Noting other authors’ commentaries and terminology, van Nieuwkerk follows Asef Bayat in calling this market “post-Islamist” – explicitly pious but unconnected to an Islamist dream of remaking the state (p. 203). I particularly appreciated how her insights into the simultaneous influence of American and Gulf consumer culture dislodge easy readings of globalization as synonymous with Americanization (pp. 227-28). The full sweep of all three sections provides a cultural history of the Islamic ...